Impact of Land Use Change on the Diurnal Cycle Climate of the Canadian Prairies - Betts , Alan K.; Desjardins, Raymond; Worth, Devon; Cerkowniak, Darrel (Emerging Issues in Environment, Geography and Earth Science Vol. 4, 2023)
AAFC [1] This paper uses hourly observations from 1953 to 2011 of temperature, relative humidity, and opaque cloud cover from 14 climate stations across the Canadian Prairies to analyze the impact of agricultural land use change on the diurnal cycle climate, represented by the mean temperature and relative humidity and their diurnal ranges. We show the difference between the years 1953-1991 and 1992-2011. The land use changes have been largest in Saskatchewan where 15-20% of the land area has been converted in the past four decades from summer fallow (where the land was left bare for 1 year) to annual cropping. During the growing season from 20 May to 28 August, relative humidity has increased by about 7%. During the first 2 months, 20 May to 19 July, maximum temperatures and the diurnal range of temperature have fallen by 1.2 \(^{°}\) C and 0.6 \(^{°}\) C, respectively, cloud cover has increased by about 4%, reducing surface net radiation by 6 W m-2, and precipitation has increased. We use the dry-downs after precipitation to separate the impact of cloud cover and show the coupling between evapotranspiration and relative humidity. We estimate, using reanalysis data from ERA-Interim, that increased transpiration from the larger area of cropland has reduced the surface Bowen ratio by 0.14-0.2. For the month on either side of the growing season, cloud cover has fallen slightly; maximum temperatures have increased, increasing the diurnal temperature range and the diurnal range of humidity.